Navigating the Legacy of Westphalia: The European Union’s Role in Managing Russian-Ukrainian Relations - Daniel Berchev (Bulgarian Journal of International Economics and Politics, 2024)
This article explores how the principles established in the Treaty of Westphalia continue to shape contemporary geopolitics, particularly in the context of the EU’s efforts to maintain stability in its eastern neighbours. Focusing on the volatile relationship between Russia and Ukraine in the 1998-2021 period, this article aims at analysing the complex dynamics between the Westphalian concept of international order, the EU and the Russian-Ukrainian conflict, shedding light on the complexities of contemporary European geopolitics. Ensuing from the research goal is the threefold research focus: 1/ Assessment of the influence of the Westphalian principles on modern European geopolitics; 2/ Assessment of EU efforts and policies to mediate conflicts and promote dialogue between Russia and Ukraine; 3/ Identification of challenges and opportunities faced by the EU in its aspirations to promote peace, stability and democracy in the region. The study puts forth the hypothesis that while the Westphalian concept of state sovereignty continues to influence international relations, the supranational model of the EU offers a unique approach to managing conflicts and promoting cooperation between European nations. By early 2022, the EU, through its diplomatic initiatives, legal mechanisms and integration efforts, is said to play a central role in mediating Russian-Ukrainian tensions and promoting the principles of peace and democracy in Eastern Europe. Methodologically, the study builds upon a comparative approach to analyse the historical context, political frameworks and diplomatic commitments related to the role of the EU in Russian-Ukrainian relations.